Pulse versus daily oral cyclophosphamide for induction of remission in ANCA-associated vasculitis: long-term follow-up. Issue 6 (29th November 2011) - Harper, Lorraine; Morgan, Matthew D; Walsh, Michael; Hoglund, Peter; Westman, Kerstin; Flossmann, Oliver; Tesar, Vladimir; Vanhille, Phillipe; Groot, Kirsten de; Luqmani, Raashid; Flores-Suarez, Luis Felipe; Watts, Richard; et al.
Abstract : Introduction: The previously reported randomised controlled trial of a consensus regimen of pulse cyclophosphamide suggested that it was as effective as a daily oral (DO) cyclophosphamide for remission induction of antineutrophil cytoplasm autoantibodies-associated systemic vasculitis when both were combined with the same glucocorticoid protocol (CYCLOPS study (Randomised trial of daily oral versus pulse Cyclophosphamide as therapy for ANCA-associated Systemic Vasculitis published de groot K, harper L et al Ann Int Med 2009)). The study had limited power to detect a difference in relapse. This study describes the long-term outcomes of patients in the CYCLOPS study. Methods: Long-term outcomes were ascertained retrospectively from 148 patients previously recruited to the CYCLOPS Trial. Data on survival, relapse, immunosuppressive treatment, cancer incidence, bone fractures, thromboembolic disease and cardiovascular morbidity were collected from physician records retrospectively. All patients were analysed according to the group to which they were randomised. Results: Median duration of follow-up was 4.3 years (IQR, 2.95–5.44 years). There was no difference in survival between the two limbs (p=0.92). Fifteen (20.8%) DO and 30 (39.5%) pulse patients had at least one relapse. The risk of relapse was significantly lower in the DO limb than the pulse limb (HR=0.50, 95% CI 0.26 to 0.93; p=0.029). Despite the increased risk of relapse in pulse-treated patients, there was no difference in renal function at study end (p=0.82). There were no differences in adverse events between the treatment limbs. Discussion: Pulse cyclophosphamide is associated with a higher relapse risk than DO cyclophosphamide. However, this is not associated with increased mortality or long-term morbidity. Although the study was retrospective, data was returned in 90% of patients from the original trial.